Relationship between symptoms of jumper's knee and the ultrasound characteristics of the patellar tendon among high level male volleyball players - Lian, O.; Holen, K. J.; Engebretsen, L.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 1996)
This study assessed the ultrasound characteristics of the patellar tendon in two groups of volleyball players, one group without knee symptoms and one group with symptoms of jumper's knee. Of 47 male elite players, 25 were diagnosed to have current and seven to have had previous symptoms of jumper's knee, as determined by clinical examination. Since some players had bilateral problems, there were 34 knees with current problems and nine with previous problems. Seven of the 30 knees with a clinical diagnosis of jumper's knee in the patellar tendon had normal ultrasound findings, and ultrasound changes believed to be associated with jumper's knee (tendon thickening, echo signal changes, irregular paratenon appearance) were observed in 12 of 51 knees without symptoms. Specific ultrasound findings such as paratenon changes, hypoechoic zones or pathological tendon thickness proximally did not correlate significantly with the degree or the duration of symptoms. This study suggests that the specificity and sensitivity of ultrasonography is low in the evaluation of patients with mild symptoms of jumper's knee.